2009
DOI: 10.1590/s1516-89132009000300007
|View full text |Cite
|
Sign up to set email alerts
|

Production of pectinases by A. niger: influence of fermentation conditions

Abstract: Response surface methodology was used for optimization of polygalacturonase (PG) and pectinesterase (PE) production in submerged fermentation by A.niger. A Central Composite Experimental Design was applied, consisting of 22 experiments, including eight central points. Variables studied were: fermentation time (24 to 120 h), pH (3.5 to 6.5) and initial concentration of pectin (5 to 20 g/l). Maximum PE production was 220 U/l, after 74 h of culture, in a medium containing 20 g/l of pectin (pH 6.5). The optimal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Some of the fungal PGs described in literature have maximum activity at pH range of 4.0-5.0 [2]. Optimal PG production was observed at pH 4.1 and lower values were obtained at pH 6.5 [29]. PG produced from Pencillium sp E9C5 presented optimum activity at pH 4.5-5.0 [14].…”
Section: Resultsmentioning
confidence: 97%
“…Some of the fungal PGs described in literature have maximum activity at pH range of 4.0-5.0 [2]. Optimal PG production was observed at pH 4.1 and lower values were obtained at pH 6.5 [29]. PG produced from Pencillium sp E9C5 presented optimum activity at pH 4.5-5.0 [14].…”
Section: Resultsmentioning
confidence: 97%
“…In the present study, citrus pectin was observed as the best carbon source to enhance pectinase production compared to other various sole carbon sources. According to Martos [ 26 ], pectin had a positive effect and linear correlation with pectinase activity whereby a higher polygalacturonase (pectinase) production was achieved when the concentration of pectin was increased. On the other hand, it is noteworthy that carbon sources such as lactose and CMC significantly suppressed pectinase production.…”
Section: Discussionmentioning
confidence: 99%
“…30 Martos et al used pectin agar as a substrate in a submerged fermentation for PG enzyme by A. niger; the activity reported was 1.03 U/mL. 31 Malvessi and da Silveira studied the production of exo-PG by Aspergillus oryzae CCT3940 in a complex media based on wheat bran, salts, and pectin as an inducer and found that maximum exo-PG activity was 45 U/mL after 64 h of cultivation at 28°C and 300 rpm. 32 These enzymes are produced by the microorganisms during the first hours of fermentation.…”
Section: Pectinase Productionmentioning
confidence: 99%